KARDIOCHIRURGIA DOROSŁYCHThoracic aortic aneurysm repair in three patients after heart transplantation: a case series - Sadowski, Jerzy; Kapelak, Boguslaw; Wierzbicki, Karol; Piatek, Jacek; Wrobel, Krzysztof; Konstanty-Kalandyk, Janusz; Bartus, Krzysztof; Wegrzyn, Piotr; Labuz, Mariola; Przybylowski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Thoracic aortic aneurysm after heart transplantation is a rare but serious complication. The authors describe 3 cases (0.6%) of thoracic aortic aneurysm during 20 years of follow-up on 485 heart transplant patients at their institution. Dissected and non-dissected thoracic aortic aneurysms, diagnosed 23 to 38 months post transplantation, were treated with surgical repair or repeat transplantation. Two patients died postoperatively of multiorgan failure, including one with septic shock. One patient was discharged in good health. Surgical repair of aortic lesions in cardiac allograft patients, including repeat transplantation in cases of allograft vasculopathy, continue to carry substantial risk to the patient.